PENGATURAN SANKSI PIDANA TAMBAHAN PENGUMUMAN PUTUSAN HAKIM TERHADAP TINDAK PIDANA PENCURIAN DENGAN KEKERASAN - Tiara Andicha Putri; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The crime of theft with violence itself is busy in the news in various media. crime against property, especially the seizure of motorbikes and other valuable objects which is accompanied by violence or which is known in everyday language as rampant once happened. Then an additional sanction is needed, namely an additional announcement of the judge's decision for the convicted person. The purpose of this study is to determine the additional criminal arrangements for announcing judges' decisions in Indonesia against violent burglaries and also the urgency to implement additional criminal announcements of judicial decisions on violent theft in these cases.This study discusses the legal systematics, the level of law synchronization, the history of law, and legal comparison. The method I use is the legal matrices system. The type of data used in this study is secondary data, namely primary legal material (the Basic Law and the Criminal Law Code), secondary legal material (books relating to the results of the research namely additional criminal arrangements announcements of judges' decisions regarding criminal acts theft with violence), and tertiary legal material. Data collection techniques using the deductive method is a way of drawing conclusions from the general to the specific nature.From the results of the study there are 2 main problems that can be concluded. Second, the urgency for the government to apply additional criminal sanctions to announce the decision of the judge is applied in Indonesia for perpetrators of theft with violence so that the perpetrators feel deterrent and do not want to repeat similar crimes or other criminal acts and also the public becomes aware of and cautious of ex-convicted criminal offense.key words: Arrangement - Additional Crimes - Announcement of Judge's Decision - Criminal Acts - Theft with violence